Androgen receptor gene methylation related to colorectal cancer risk. Issue 7 (July 2019) - Xia, Tingting; Sun, Hongru; Huang, Hao; Bi, Haoran; Pu, Rui; Zhang, Lei; Zhang, Yuanyuan; Liu, Ying; Xu, Jing; Onwuka, Justina Ucheojor; Liu, Yupeng; Cui, Binbin; et al.
Abstract : According to its incidence patterns, colorectal cancer (CRC) tends to occur more frequently in males than in females, and the evidence shows that CRC is a hormone-related tumor. These findings indicate that androgen receptor ( AR ) gene methylation might be important for the regulation of the CRC risk in the different sexes. We used a case–control study to investigate the association between AR methylation in peripheral blood (PBL) and CRC risk. A cohort study was conducted to analyze the effect of AR methylation levels in both PBL and tissue on the prognosis of CRC. AR methylation levels were detected using methylation-sensitive high-resolution melting (MS-HRM). The results indicate that the hypomethylation of AR was significantly associated with the risk of CRC (OR = 1.869, 95% CI: 1.629–2.141, P < 0.001), and the results remained similar after adjusting for the propensity score (PS) (OR = 1.344, 95% CI: 1.147–1.575, P < 0.001) and PS matching (OR = 1.138, 95% CI: 1.000–1.292 P = 0.049). The hypomethylation of AR was significantly associated with CRC in males (OR = 2.309, 95% CI: 1.200–4.245; P = 0.012) but not females (OR = 1.000, 95% CI: 0.567–1.765; P = 0.999). The methylation status of AR in PBL and tissue does not seem to be associated with prognosis in colorectal cancer (OR = 1.425, 95% CI: 0.895–2.269, P = 0.135; OR = 0.930, 95% CI: 0.674–1.285, P = 0.661). We conclude that AR hypomethylation in PBL is associated with a high risk of CRC and may serve as a biomarker. Further studies involving large sample sizes are needed to validate the results of this study.